2014
DOI: 10.1002/pca.2533
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenanthrene Derivatives in Aerides rosea (Orchidaceae) Using the Combined Systems HPLC–ESI–HRMS/MS and HPLC–DAD–MS–SPE–UV–NMR

Abstract: Nine secondary metabolites were characterised in A. rosea stems, utilising HPLC systems combined with high-resolution analytical systems. Two of them are newly described phenanthrene derivatives: aerosanthrene (5-methoxyphenanthrene-2,3,7-triol) and aerosin (3-methoxy-9,10-dihydro-2,5,7-phenanthrenetriol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Thus, glomerular mesangial cells cultured under high glucose conditions were employed as a model of DN [22,23]. Gigantol is a phenolic substance extracted from plants in the genus Dendrobium [14]. As plants of the Dendrobium genus are commonly being used to treat diabetes mellitus in Traditional Chinese Medicine [26], the current study used the in vitro approach to examine the potential effects of gigantol on the high glucose-induced glomerulus mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, glomerular mesangial cells cultured under high glucose conditions were employed as a model of DN [22,23]. Gigantol is a phenolic substance extracted from plants in the genus Dendrobium [14]. As plants of the Dendrobium genus are commonly being used to treat diabetes mellitus in Traditional Chinese Medicine [26], the current study used the in vitro approach to examine the potential effects of gigantol on the high glucose-induced glomerulus mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the chemical components and pharmacology of Dendrobium plants have been studied to provide scientific proof to justify the medicinal use in the treatment of diseases [13]. Gigantol (3′,4-dihydroxy-3,5′-dimethoxybibenzyl) is a bibenzyl-type phenolic compound isolated from several medicinal orchids, which contains active phenolic hydroxyl groups, displays aromatic and hydrophobic characteristics, and exerts a wide range of pharmacological activities [14]. Previous studies have shown that gigantol has several bioactivities including anti-osmotic [15], antioxidant [15], antispasmodic [16], antinociceptive and anti-inflammatory effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…The purification of vandaterosides I and II was monitored by TLC and HPLC analyses. However, to confirm unambiguously their identity, the final fractions obtained were analysed by a targeted HPLC–ESI‐HRMS/MS method previously developed in our group . Results confirmed unequivocally the identity of vandateroside I and II.…”
Section: Resultsmentioning
confidence: 77%
“…The identity of isolated vandaterosides I and II was confirmed by a validated targeted HPLC–ESI‐HRMS/MS method, previously developed by our team . Internal standards were injected separately to obtain their HRMS/MS spectra.…”
Section: Methodsmentioning
confidence: 99%
“…It also enables structural identification of many secondary metabolites present in the complex matrix, in a single run (dereplication of complex matrices). 27 …”
Section: Phytochemical Analysismentioning
confidence: 99%